2016
DOI: 10.1038/ejcn.2015.222
|View full text |Cite
|
Sign up to set email alerts
|

Folate and vitamin B-6 status are not associated with homocysteine, oxidative stress and antioxidant capacities in patients with hepatocellular carcinoma

Abstract: The purpose of this study was to study the effects of serum folate and plasma pyridoxal 5'-phosphate (PLP) on plasma homocysteine, oxidative stress and antioxidant capacities in 44 hepatocellular carcinoma (HCC) patients and 56 healthy controls. The responses of folate, vitamin B-6, homocysteine, oxidative stress and antioxidant enzyme activities in HCC patients before and after tumor resection were also determined. Patients with HCC before tumor resection had significantly lower folate, PLP, homocysteine, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…24,25 Studies have shown an inverse association between blood folate levels and HCC risk. 2630 Therefore, folate status also may be associated with HCC prognosis. More advanced stage HCC patients have lower folate levels than those with earlier stage disease, but no study examined the role of circulating folate in survival of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Studies have shown an inverse association between blood folate levels and HCC risk. 2630 Therefore, folate status also may be associated with HCC prognosis. More advanced stage HCC patients have lower folate levels than those with earlier stage disease, but no study examined the role of circulating folate in survival of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Lin CC et al [ 19 ] showed that plasma level of folate in HCC patients was significantly lower compared to healthy controls, in spite of very small sample size in their study (40 cases and 20 controls). Recently, Cheng et al [ 20 ] showed that HCC patients at preresection had lower serum folate than that of control groups. Chang et al [ 21 ] also observed an inverse association between plasma folate levels and liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, scholars 38 have found that VB6 is related to the metabolism of H 2 S, H 2 S 2 , cystine, cysteine, homocysteine, cystine sulfide, and methionine in the metabolic reprogramming of liver cancer. 39 Many clinical trials [40][41][42] have observed an anti-hepatocellular carcinoma effect by directly…”
mentioning
confidence: 99%